Social Cognitive Constructs Are Just as Stable as the Big Five Between Grades 5 and 8 - Sven Rieger; Richard Göllner; Marion Spengler; Ulrich Trautwein; Benjamin Nagengast; Brent W. Roberts (SAGE Publishing, 2017)
Personality traits and social cognitive variables are central constructs in psychological research. It is often assumed that personality traits are less changeable than social cognitive variables, and thus interventions usually tend to focus on the latter. However, these assumptions about the mutability of personality and social cognitive variables have never been tested side-by-side in a longitudinal study. Using a large longitudinal study with four time points and N = 3,876 students in 136 classes (99 schools), we compared the mutability of the Big Five personality traits and social cognitive constructs more often described as socioemotional skills or motivational variables (individual interest, self-concept, and academic effort in the school subjects math, English, and German). The results indicated that there are no marked differences between personality traits and social cognitive constructs across multiple indicators of stability or changeability.